STUDY OF SOME FIXED EFFECT IN MILK PRODUCTION AND GROWTH TRAITS IN LOCAL BLACK GOATS - Ruaa Nasrat Ali; Zaid Mohammed Mahdi (European Journal of Agricultural and Rural Education, 2022)
The study was conducted on a sample of 34 local goats from a breeder in Canaan sub-district / Diyala governorate for the period 13/11/2021 to 1/5/2022. The objective of the present study was to study of some effect factors in milk production (daily milk production- DMY and total milk production-TMY) and growth traits (birth, weaning weight and weight gain pre weaning). The General linear model (GLM) within the SAS (2012) computer package was used to analyze the data. The resulted showed a significant difference of sex in weaning weight (WWT), as males superiority (14.67) kg over females (13.19) kg, while the type of birth had a significant difference for all growth traits, as single births superiority twins in Birth weight (BWT) (2.95 and 2.64) kg, respectively, as for WWT and weight gain (WTG), twin births (15.87 and 15.46) kg, respectively, superiority single births (13.48 and 10.53) kg, respectively. As for the month of birth, there was a significant difference for all growth traits, The highest significant for the month of January was in WWT and WTG over the rest of study months (19.88 and 19.42) kg respectively, while significant of December for BWT (3.32 kg). As for the traits of milk production, the sex of newborn and type of birth had non significant effect. There while significant effect for the month of birth on the traits of DMY and TMY but month of birth was significant different, was in superiority of January (0.477 and 373.02) kg, respectively.